The Coagulation Abnormalities in Systemic Lupus Erythematosus - Gonyea, L; Herdman, R; Bridges, R. A (Thrombosis and Haemostasis, 1968)
An anticoagulant occurring in 4 of 6 patients with SLE has been demonstrated by a sensitive assay utilizing an ammonium sulfate fraction of serum. The anticoagulant functions as an inhibitor of the activation of prothrombin. No species specificity was demonstrable. The inhibitor behaves clinically and chromatographically as an immunoglobulin, although an attempt to demonstrate directly the antibody nature of the inhibitor was not successful.A severe, apparently independent, decrease in the level of prothrombin was observed in the patient with hemorrhagic symptoms. In contrast to the anticoagulant activity, the low prothrombin has persisted during treatment.